Initial Invasive Versus Conservative Management of Stable Ischemic Heart Disease in Patients With a History of Heart Failure or Left Ventricular Dysfunction: Insights From the ISCHEMIA Trial. Issue 18 (3rd November 2020) - Lopes, Renato D.; Alexander, Karen P.; Stevens, Susanna R.; Reynolds, Harmony R.; Stone, Gregg W.; Piña, Ileana L.; Rockhold, Frank W.; Elghamaz, Ahmed; Lopez-Sendon, Jose Luis; Farsky, Pedro S.; Chernyavskiy, Alexander M.; Diaz, Ariel; et al.
Abstract : Background: Whether an initial invasive strategy in patients with stable ischemic heart disease and at least moderate ischemia improves outcomes in the setting of a history of heart failure (HF) or left ventricular dysfunction (LVD) when ejection fraction is ≥35% but <45% is unknown. Methods: Among 5179 participants randomized into ISCHEMIA (International Study of Comparative Health Effectiveness With Medical and Invasive Approaches), all of whom had left ventricular ejection fraction (LVEF) ≥35%, we compared cardiovascular outcomes by treatment strategy in participants with a history of HF/LVD at baseline versus those without HF/LVD. Median follow-up was 3.2 years. Results: There were 398 (7.7%) participants with HF/LVD at baseline, of whom 177 had HF/LVEF >45%, 28 HF/LVEF 35% to 45%, and 193 LVEF 35% to 45% but no history of HF. HF/LVD was associated with more comorbidities at baseline, particularly previous myocardial infarction, stroke, and hypertension. Compared with patients without HF/LVD, participants with HF/LVD were more likely to experience a primary outcome composite of cardiovascular death, nonfatal myocardial infarction, or hospitalization for unstable angina, HF, or resuscitated cardiac arrest (4-year cumulative incidence rate, 22.7% versus 13.8%; cardiovascular death or myocardial infarction, 19.7% versus 12.3%; and all-cause death or HF, 15.0% versus 6.9%). Participants with HF/LVD randomized to the invasive versus conservative strategy had a lower rate of the primary outcome (17.2% versus 29.3%; difference in 4-year event rate, −12.1% [95% CI, −22.6 to −1.6%]), whereas those without HF/LVD did not (13.0% versus 14.6%; difference in 4-year event rate, −1.6% [95% CI, −3.8% to 0.7%]; P interaction = 0.055). A similar differential effect was seen for the primary outcome, all-cause mortality, and cardiovascular mortality when invasive versus conservative strategy–associated outcomes were analyzed with LVEF as a continuous variable for patients with and without previous HF. Conclusions: ISCHEMIA participants with stable ischemic heart disease and at least moderate ischemia with a history of HF or LVD were at increased risk for the primary outcome. In the small, high-risk subgroup with HF and LVEF 35% to 45%, an initial invasive approach was associated with better event-free survival. This result should be considered hypothesis-generating. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01471522. Abstract : Supplemental Digital Content is available in the text.